Ethnopharmacological study of the Selected Tribal Medicinal Plants of the Tboli People in Lake Sebu, South Cotabato - Alvin Q. Larida; Johnryk B. Soldevilla; Christopher John B. Ursabia; Dominique Rose C. Blanco (Journal of Science and Science Education, 2022)
Around 80% of people around the world have practiced the use of ethnopharmacological medicine. Tboli tribe of Lake Sebu, South Cotabato, Philippines recognized medicinal plants for healing. There were two identified plants by the Tboli people, the Bulok bukay (Stachytarpheta jamaicensis) and Kluonmabu (Ageratum conyzoides L.) as a potential medicine for wound healing. The plants underwent antimicrobial analysis, phytochemical screening, and functional groups detection through FTIR. The zone of inhibition for Bulok bukay showed antimicrobial potential in all concentrations. Kluonmabu observed as not as effective as the other plant against S. aureus. With the p = 0.0641 at 0.05 level of significance, Bulok bukay showed to be effective against bacteria and comparable with a commercial antibiotic. Furthermore, phytochemical properties for both plants have been observed with more components of alkaloids and terpenoids in Bulok bukay. FTIR confirmed as well that two plants have the potential presence of functional groups against bacteria